2015
DOI: 10.1038/srep14537
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Dual-wavelength Thulium-doped Fiber Laser at 1.9 μm Using Photonic Crystal Fiber

Abstract: A stable dual-wavelength thulium-doped fiber laser operating at 1.9 μm using a short length of photonic crystal fiber (PCF) has been proposed and demonstrated. The photonics crystal fiber was 10 cm in length and effectively acted as a Mach-Zehnder interferometry element with a free spectral range of 0.2 nm. This dual-wavelength thulium-doped fiber laser operated steadily at room temperature with a 45 dB optical signal-to-noise-ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Tunable sources near 2 μm are also of interest due to their utility in applications such as speckle-imaging [2][3], eye-safe differential absorption lidar [4][5], range finding [6], coherent Doppler wind lidar [7], and terahertz (THz) difference-frequency-generation (DFG) [8]. Wavelength generation in the 2-μm region has been achieved using Ho 3+ -doped, Tm 3+ -doped, or Tm 3+ :Ho 3+ co-doped fiber lasers [9][10], mode-locked Tm:CaYAlO4 (Tm:CYA) laser [11], near-degenerate optical parametric oscillators (OPOs) [12], and, more recently, intracavity OPOs in two-crystal walkoff compensation scheme [13]. Laser sources at ~2 μm and beyond are also necessary for pumping long-wave mid-infrared (mid-IR) OPOs and DFG sources based on non-oxide nonlinear materials such as ZnGeP2, AgGaS2, AgGaSe2 and quasi-phase-matched orientationpatterned gallium arsenide (OP-GaAs) [12,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Tunable sources near 2 μm are also of interest due to their utility in applications such as speckle-imaging [2][3], eye-safe differential absorption lidar [4][5], range finding [6], coherent Doppler wind lidar [7], and terahertz (THz) difference-frequency-generation (DFG) [8]. Wavelength generation in the 2-μm region has been achieved using Ho 3+ -doped, Tm 3+ -doped, or Tm 3+ :Ho 3+ co-doped fiber lasers [9][10], mode-locked Tm:CaYAlO4 (Tm:CYA) laser [11], near-degenerate optical parametric oscillators (OPOs) [12], and, more recently, intracavity OPOs in two-crystal walkoff compensation scheme [13]. Laser sources at ~2 μm and beyond are also necessary for pumping long-wave mid-infrared (mid-IR) OPOs and DFG sources based on non-oxide nonlinear materials such as ZnGeP2, AgGaS2, AgGaSe2 and quasi-phase-matched orientationpatterned gallium arsenide (OP-GaAs) [12,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different dualwavelength TDFLs approaches at the 2-μm wavelength band were reported. These configurations are based on fiber Bragg Gratings (FBG) [1]- [9], spatial mode beating effect [10]- [12], carbon nanotubes [13], photonic crystal fibers [14], and fiber interferometers [1], [15]- [17], among others. Liu of a TDFL based on a polarization maintaining (PM) FBG and a PM Fabry-Perot filter [1].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al proposed a stable dual-wavelength TDFL based on cascaded fiber Bragg gratings [6]. Soltanian et al achieved stable dual-wavelength operation of a TDFL operating at 1.9 μm by using a 10 cm length of photonic crystal fiber [13]. Nevertheless, most of the previously reported dual-wavelength fiber lasers based on TDF exhibit laser emission with wavelengths below of 2 μm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al proposed a dual-wavelength TDFL incorporating a Sagnac loop mirror and tunable operation was achieved with a polarization controller inside the cavity [9]. Recently, Soltanian et al demonstrated a dual-wavelength fiber laser operating at 1.9 μm with a photonic crystal fiber-based Mach-Zehnder interferometer [10].…”
Section: Introductionmentioning
confidence: 99%